Colorectal cancer in pregnancy. Case reports - Haro Sánchez, Silvia Ivonne (2023)
Colon rectal cancer (CRC) during pregnancy is a rare neoplasia, with an incidence between 0.07-0.1% in the population. For an early diagnosis, a high suspicion is necessary and with it, timely diagnostic tests are carried out. When there is no suspicion and no diagnosis is sought, the prognosis is usually poor since it is often in an advanced state. We present the cases of two pregnant women aged 27 and 31 diagnosed with moderately differentiated colorectal adenocarcinoma at 29 and 30 weeks of gestation, respectively. Due to the importance of making an opportune diagnosis to improve the survival of the patients, a search of information was carried out in the literature in relation to the diagnosis, management and prognosis of this pathology.